DIFFERENCES IN LOWER LIMB MUSCLE ACTIVITY DURING LUNGE MOVEMENTS IN FENCING ATHLETES WITH AND WITHOUT INJURY HISTORY - Adhi, Wisnu Prasetyo; Susilo, Taufik Eko; Dewangga, Mahendra Wahyu (Rehabilitation and Recreation, 2025)
Purpose the Work: This study aimed to investigate differences in lower limb muscle activity during lunge movements among fencing athletes with and without a history of lower extremity injury, with an emphasis on gender-based variations. Understanding these differences may help refine training and rehabilitation strategies tailored to athlete needs. Method and Materials: A total of 24 fencing athletes (12 males and 12 females) aged 15–24 years were recruited and categorized into injured and non-injured groups. Surface electromyography (sEMG) was used to measure the activity of seven lower limb muscles – rectus femoris, vastus medialis, vastus lateralis, biceps femoris, semitendinosus, gastrocnemius medialis, and gastrocnemius lateralis – during lunge movements. Muscle activity data were analyzed using independent t-tests via SPSS version 26. Results: In male athletes, significantly higher muscle activity was observed in the non-injured group for the rectus femoris, vastus medialis, vastus lateralis, and gastrocnemius lateralis (p < 0.05). In contrast, female athletes with no injury history showed significantly greater muscle activation in the rectus femoris, vastus medialis, vastus lateralis, biceps femoris, semitendinosus, and gastrocnemius medialis (p < 0.05). Some muscle groups, such as the biceps femoris and semitendinosus in males and the gastrocnemius lateralis in females, did not differ significantly between groups. Conclusion: Lower extremity injuries result in reduced muscle activity during lunge movements, with broader effects observed in female athletes. These findings underscore the importance of considering gender differences in the development of injury prevention and rehabilitation programs for fencing athletes.